Traveling Concepts in the Classroom: Experiences in Interdisciplinary Education - Diphoorn, Tessa; McGonigle Leyh, Brianne; Knittel, Susanne C.; Huysmans, Martijn; Goch, Merel Van (Journal of Interdisciplinary Studies in Education, 2023)
Interdisciplinary research is widely valued and practiced within higher education. However, there is less attention on interdisciplinary teaching and learning, and existing examples often focus on problem-based approaches. The purpose of this special issue is to explore the potential of a concept-based approach to interdisciplinary education, working with the notion of traveling concepts. Traveling concepts refer to the metaphorical traveling or use of concepts within and between disciplines that impacts their meaning, reach, and operational value. This special issue introduction provides a theoretical and conceptual framework around traveling concepts, which special issue contributions then use to reflect on specific interventions. These reflections highlight the importance of interdisciplinarity beyond a problem-solving frame and provide concrete classroom examples to inspire teachers.